Consultant presence during major obstetric haemorrhage. (18th April 2012) - Harrity, C; Ahmed, S; O'Reilly, H; Cheah, M; Byrne, B
Abstract : Background: Consultant presence on labour ward can improve patient outcomes, with recommendations for on-site cover of 60 hours/week in units with ≥5, 000 births/year. The study aims to assess the potential impact of introducing these recommendations on the management of major obstetric haemorrhage (MOH) in a unit with >9000 deliveries/year and only 24hr/week of dedicated consultant labour ward sessions. Methods: Data from MOH cases from 01/01/09-30/06/11 was collected using a validated proforma. MOH was defined as an EBL of ≥2.5L, transfusion of ≥ 5 units of Red Cell Concentrate, or treatment of coagulopathy. Results: 70 MOH cases were identified in the study period, with consultant obstetrician presence in 59(84.3%), and consultant anaesthetist presence in 43(61.4%). Consultant obstetrician presence varied depending on the cause of MOH (100% for placenta accreta and coagulopathy, 76.9% for uterine atony, 50% for abruption) and complexity of treatment instigated (100% for hysterectomy, B-Lynch or internal iliac ligation, 86.9% for intrauterine balloon, and 70.6% for RPOC). Consultant obstetricians were present in cases with a higher EBL (3.7L vs 2.6L) and greater requirement for blood transfusion (5.0 vs 3.5 units). The overall rate of ICU admission was 1.4%, 90% were admitted to HDU, and there were no maternal deaths. 47% of cases occurred outside normal working hours (9-5 Mon-Fri). Conclusions: Consultant presence during MOH is already high, and implementation of 60-hour cover may not influence care of these patients, especially as a large proportion occur out-of-hours. Improved consultant presence may possibly benefit outcomes in other areas.